Intervenção educativa para o autocuidado com os pés de idosos com diabetes mellitus - Marques, Marilia Braga (2015)
The diabetic foot is one of the complications of Diabetes Mellitus (DM) and it significantly affects the elderly population with DM; thus developing actions for prevention and encouragement of self-care with the feet is essential to prevent such complication. The present study aimed at evaluating the effectiveness of an educational intervention for self-care with the feet of elderly people with DM. Quasi-experimental study carried out with two groups: experimental group (GE) and control group (GC), with conduction of pre-test and post-test. The study was developed from March 2014 to January 2015 in the city of Fortaleza, in two primary health care units. The sample consisted of 150 elderly, 93 in GE and 57 in CG, but 103 completed all phases of the study, 53 in GE and 50 in GC. To collect data, it was used the Sociodemographic and Clinical form; Risk Assessment Form for the diabetic foot, Diabetes Self-Care Activities Questionnaire (QAD), Appraisal of self-care agency scale” (ASA- A), the Questionnaire on knowledge and behavior for essential care foot. For intervention, it was used two flip charts, one on treatment for DM and another named “Vamos pegar no pé com amor e carinho”. The ethical aspects of the Resolution 466/12 were respected at all stages of the study. The results showed that the average age was 68.71 (± 6.10) years, 81.3% female, with an average education level of 6.04 (± 4.27) years of study, 74% had individual and family income ranging from 1 to 2 minimum wages. The average time of diagnosis was 9.56 years, 50.7% had hypertension, 93.3% were using oral anti-diabetic agent, 64% used insulin, 34.7% did physical activity. After the educational intervention in the GE, there was an increase of self-care in diabetes related to healthy eating, nutritional guidance and examination of the feet. Regarding knowledge about foot care, the following points showed statistical significance: examination of the feet, use of garter belt, what should be used to wipe the feet, cuticle removal, appropriate time to buy shoes, what should be used to rub the feet, kind of indicated socks, characteristics of the socks, use of moisturizing on the feet and internal aspect of the shoe. In the GC, no aspect had statistical significance. Regarding the behavior for foot care, the GE showed behavioral change on washing and moisturizing feet, internal aspect of the shoe, cuticle removal and examination of feet; in the GC, a representative number of participants went on to examine the feet. We conclude that educational intervention favored the increase of self-care with the feet of the elderly with DM in several aspects evaluated after the intervention. It is worth highlighting the importance of developing group activities performed by nurses directed to the elderly in primary care, considering the particularities of this age group, mainly aiming at preventing disabilities and complications related to chronic diseases, in particular, the DM.